Application of zein and chitosan in the development of a colon-specific delivery system - Ricardo Fiori Zara, Paulo Rodrigo Stival Bittencourt, Tatiana Shioji Tiuman, Vanderson Galan, Fábio Pinheiro de Souza, Érica Rosane Kovalczuk Ávila (Journal of Applied Pharmaceutical Science, 2021)
Drug release in the colon is a therapeutic alternative for pathologies that affect this organ, for absorption of peptide drugs and proteins, and in chronopharmacotherapy. Systems for this purpose should be formulated considering the obstacles of the gastrointestinal tract. Strategies used consider characteristics such as pH, enzymatic activity, microflora, and transit time. This work aims to present a system to deliver drugs directly to the colon using the natural polymers zein and chitosan. The biopolymers were prepared with the objective of obtaining effective polymer dispersions to be applied in the coating of tablets and evaluated for in vitro dissolution profile. The polymer films obtained by casting were characterized by Fourier-transform infrared spectroscopy, thermal analysis, mechanical analysis, and water vapor transmission. The results obtained demonstrate that zein can be used as a sealing coat to separate incompatible materials and as a barrier against moisture. They also show that chitosan is specifically degraded by the colonic flora and, when associated with ethyl cellulose, can be applied as support for the colon-specific delivery.
Keywords: Biopolymers, drug delivery device, selectivity of drug delivery, routes of drug administration, controlled release.